Preexposure effects in spatial learning: From gestaltic to associative and attentional cognitive maps - Edward S. Redhead; José Prados (Psicológica, 2002)
In this paper a series of studies and theoretical proposals about how
preexposure to environmental cues affects subsequent spatial learning are
reviewed. Traditionally, spatial learning had been thought to depend on
gestaltic non-associative processes, and well established phenomena such as
latent learning or instantaneous transfer have been taken to provide evidence
for this sort of cognitive mapping. However, reviewing the literature
examining these effects reveals that there is no need to advocate for gestaltic
processes since standard associative learning theory provides an adequate
framework for accounting for navigation skills. Recent studies reveal that
attentional processes play a role in spatial learning. The need for an
integrated attentional and associative approach to explain spatial learning is
discussed.